The role of repetition and reinforcement in school-based oral health education-a cluster randomized controlled trial. (December 2015) - Haleem, Abdul; Khan, Muhammad; Sufia, Shamta; Chaudhry, Saima; Siddiqui, Muhammad; Khan, Ayyaz
Abstract Background Repetition and reinforcement have been shown to play a crucial role in the sustainability of the effect of Oral Health Education (OHE) programs. However, its relevance to school-based OHE imparted by different personnel is not depicted by the existing dental literature. The present study was undertaken to determine the effectiveness of the repeated and reinforced OHE (RR-OHE) compared to one-time OHE intervention and to assess its role in school-based OHE imparted by dentist, teachers and peers. Methods The study was a cluster randomized controlled trial that involved 935 adolescents aged 10-11 years. Twenty four boys' and girls' schools selected at random in two towns of Karachi, Pakistan were randomly assigned to three groups to receive OHE by dentist (DL), teachers (TL) and peer-leaders (PL). The groups received a single OHE session and were evaluated post-intervention and 6 months after. The three groups were then exposed to OHE for 6 months followed by 1 year of no OHE activity. Two further evaluations at 6-month and 12-month intervals were conducted. The data were collected by a self-administered questionnaire preceded by a structured interview and followed by oral examination of participants. Results The adolescents' oral health knowledge (OHK) in the DL and PL groups increased significantly by a single OHE session compared to their baseline knowledge (p  < 0.05) and the increase was sustained over 6 months. Although one-time OHE resulted in a significant improvement in adolescents' oral health behavior (OHB) related to the prevention of gingivitis in the two groups (p  < 0.05), no significant change was observed in their behavior towards prevention of oral cancer. One-time teacher-led OHE was ineffective in improving adolescents' OHK and OHB. The oral hygiene status (OHS) of the participants in all three groups did not change statistically after one-time OHE. The OHK, OHB and OHS indices increased significantly 6 months after RR-OHE than the initial scores (p  < 0.001) irrespective of OHE strategy. Although the OHK scores of the DL and PL groups decreased significantly at 12-month evaluation of RR-OHE (p  < 0.05), the said score of the TL group; and OHB and OHS scores of all three groups remained statistically unchanged during this period. Conclusions The repetition and reinforcement play a key role in school-based OHE irrespective of educators. The trained teachers and peers can play a complementary role in RR-OHE.